The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2019
DOI: 10.1177/1538192719835681
|View full text |Cite
|
Sign up to set email alerts
|

Descriptive Analysis of Graduate Enrollment Trends at Hispanic-Serving Institutions: 2005-2015

Abstract: Hispanic-Serving Institutions (HSIs) are postsecondary institutions that enroll 25% Latinx undergraduate students, with little emphasis on graduate enrollment. Graduate enrollment was explored at HSIs, looking at trends over 10 years. Descriptive analyses and data from the Integrated Postsecondary Education Data System (IPEDS) were used, shedding light on enrollment inequities between Latinx undergraduate and graduate students. This study has implications for graduate HSIs, which can become primary educators o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
16
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 16 publications
(17 citation statements)
references
References 17 publications
1
16
0
Order By: Relevance
“…In this study, URM students represented almost 35% of the undergraduate students but only 14% of the GTA population. This is consistent with other studies that have reported Latinx undergraduate student enrollment is higher than Latinx graduate student enrollment at HSIs ( Garcia, 2017 ; Garcia and Guzman-Alvarez, 2019 ). Similarly, the number of URM students earning bachelor’s degrees in STEM is greater than the number earning doctoral degrees in STEM ( Estrada et al.…”
Section: Discussionsupporting
confidence: 93%
“…In this study, URM students represented almost 35% of the undergraduate students but only 14% of the GTA population. This is consistent with other studies that have reported Latinx undergraduate student enrollment is higher than Latinx graduate student enrollment at HSIs ( Garcia, 2017 ; Garcia and Guzman-Alvarez, 2019 ). Similarly, the number of URM students earning bachelor’s degrees in STEM is greater than the number earning doctoral degrees in STEM ( Estrada et al.…”
Section: Discussionsupporting
confidence: 93%
“…This argument has been further stressed by researchers who state that HSIs must provide culturally sustaining practices that promote equitable outcomes (Malcom-Piqueux & Bensimon, 2015), including culturally relevant curricula and advising practices (Garcia & Okhidoi, 2015). Elements of the organizational culture and campus climate may include the compositional diversity of the faculty (Contreras, 2017) and graduate student population, which is blatantly white when compared with the undergraduate population (Garcia & Guzman-Alvarez, 2019), while some claim that all faculty and institutional leaders must become agents of change who work toward equitable outcomes and experiences of all students at HSIs (Malcom-Piqueux & Bensimon, 2015;Garcia, 2019).…”
Section: Conceptual Framework To Understand Hsis and Servingnessmentioning
confidence: 99%
“…Some literature discusses the use of IPEDS data to help institutions with benchmarking, or making comparisons with other institutions [9][10][11]. Other research used IPEDS data to determine true college costs [12], to examine cultural and racial equity in enrollment and outcomes [13,14], to examine productivity or to develop systems to measure productivity of higher education institutions [15], to examine graduation rates [16], examine completion and credentials by specific demographics and categories [17], and to examine the effects of online programs on state appropriations [18].…”
Section: Integrated Postsecondary Data Systemmentioning
confidence: 99%